The Role of Women in Supporting the Family Economy in the Sesaot Forest Area - Erwanti, Annisa Aura; Markum; Setiawan, Budhy (Mataram University, 2024)
Research This aim For identify variety sources income women to support economy family, analyze contribution income Woman to income economy family, and analyze factor supporting and inhibiting business productive Woman. Method study Which used namely the descriptive method and the census method, namely interview structured to 34 respondents in the Sesaot Forest Area on month October 2023. Respondent elements include women who run non-timber forest product businesses, who are members of the Women's business group, including NTFP businesses in the form of Processed Coffee Grounds, Processed Chips, and Processed Cassava Rengginang, and non-NTFP businesses include Kiosk Traders, Laundry, Credit Traders, Fried Food Traders, Employees, Tailors, Trade (Fashion), Resellers, Farmers, Mobile Food Sellers, Palm Sugar Processors, and Rujak Sellers. The average income value from NTFP businesses is IDR 855,706, and non-HHBK is IDR-1,112,089. The contribution value of women's income from NTFP businesses to family income is an average of 37.10%/month. Meanwhile, the income value of non-NTFP women's contribution to the family economy in Forest Areas has an average value of 18.61%/month. Supporting factors for women's productive businesses are equipment, raw materials, profits and skills. Supporting factors business productive Woman namely capital, products and markets.